The acquisition of water storage facilities in the Abay River Basin, Ethiopia - Irit Eguavoen (University of Bonn, Center for Development Research (ZEF), 2009)
This paper provides a typology of water storage technologies in the Abay sub-basin of the Blue Nile River basin from the 1960s to the present-day. Based on a literature review and project document review, various ways of facility creation and acquisition are analysed with regard to their social dynamics, political interest and project outcome. As a result, specific research needs in the social-political domain are formulated and topics and indicators for a comparative social-political assessment of the facility acquisition processes developed.
urn:nbn:de:101:1-2009050564
Keywords: 330; Blue Nile; Ethiopia; climate change; water storage; preparation of social-political assessment